Policing the 'progressive' city: The racialized geography of drug law enforcement. (August 2013) - Lynch, Mona; Omori, Marisa; Roussell, Aaron; Valasik, Matthew
This article explores selective drug law enforcement practices in a single municipality, San Francisco, where racial disproportionality in drug arrest rates is among the highest in the United States. We situate this work in the vein of recent case-study examinations done in Seattle, Cleveland, and New York to help build a more nuanced picture of how the local geography of policing drugs produces racialized outcomes. Within this, we examine how historically embedded local politics shape the varied styles and structures of policing that result in racially discriminatory enforcement patterns. Our goal is to begin sketching out a robust framework of 'place' as an orientation for examining discretionary local policing practices, especially as they impact marginalized groups and communities of color.